Pengaruh Budaya Organisasi dan Ketidakpastian Lingkungan terhadap Penerapan Praktik Akuntansi Manajemen pada Usaha Kecil dan Menengah - Try Meilinda; Dian Fitria Handayani (Universitas Negeri Padang, 2024)
This paper aims to determine the influence of organizational culture and environmental uncertainty on the implementation of management accounting practices in SMEs in Limapuluh Kota Regency. Objective data was taken from a questionnaire with a sample of 100 companies. The statistical test tool used is SPSS version 24. Findings from data analysis show that an important factor influencing the level of implementation of management accounting practices in SMEs is organizational culture. Organizations that have good commitment and vision in achieving their goals will be more flexible in accepting reforms, including in implementing management accounting practices. Apart from that, the environmental uncertainty felt by companies also encourages companies to use various kinds of management accounting practices in order to maintain and sustain their business. Previous research has studied various contingent factors that influence the implementation of PAM in SMEs, but there is still little previous research that studies the influence of culture in implementing corporate PAM, especially in small and medium enterprises.